Experiences of women receiving high dose rate brachytherapy for cervical cancer at ocean road cancer institute Dar-es-salaam Tanzania - Francis Kazoba; Nazima Dharsee (Global Journal of Cancer Therapy - Peertechz Publications, 2020)
The objective of this study was to present a descriptive summary of the experiences of women treated with high dose rate brachytherapy for cervical cancer. A qualitative descriptive study design was used and 50 women who undergo high dose rate brachytherapy at Ocean Road Cancer Institute (ORCI) in Dar-es-salaam were selected. Qualitative interviewer administered questionnaire was used for data collection from cervical cancer patients treated between April 2019 to July 2019 for descriptive and thematic analysis of data. Qualitative interviewer administered questioning was done from which three themes arose: the patient perception, expectation and impressions, informational need, and psychological experiences. Many patients had good perception about brachytherapy although their first impression was bad. The study found the importance of provision of procedure information to patient which seems to improve their treatment experiences. The psychological experiences faced by patients before and during treatment included pain, distress, fear, humiliation and anxiety Pain was a major problem, as the preventative medication participants received had low efficiency in pain prevention hence did not protect them from experiencing pain. Opening and hanging their legs was a humiliating experience aggravated by the presence of doctors and nurses. Their belief that brachytherapy can cure their disease comforted them and gave them courage to endure the treatment, whilst caring staff comforted and supported them. In addition to individualized patient education, nurses should assess the level of pain women experience before, during and after receiving brachytherapy and advice the revision of pain management protocols.